KECERDASAN INTERPERSONAL SISWA PELAKU BULLYING DI SD NEGERI TONOGORO KULON PROGO - Ahmad Budi Nugroho; Heri Maria Zulfiati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
The purpose of the research is to describe the interpersonal intelligence of the students conducting bullies and the factors influencing the bullies. The research is qualitative research applying a case study. The research is done at Tonorogo Elementary School. The subjects of the research are bullying-doers, the victims and teachers while the object is the interpersonal intelligence of the students conducting bullies. The technics of data collecting are observations, interviews and documentations. The instruments of the research are the researcher, observation and interview guides. The validity test of the data applies triangulation technic, resources and time. Data analysis technic uses interactive model that is data collection, data reduction, data display, and drawing conclusion. The result of the research descriptively shows that the interpersonal intelligence of the students conducting bullies at school can be categories worse based on dimension of the interpersonal intelligence that covers social sensitivity, social insight and social communication. The doers have been proven to do both physical and verbal attacks to others so that they fail to have positive relationship in their social environments. Interest and study achievements of the bullying-doers are the cause and effect of the bad interpersonal intelligence of the bullying-doers. The school has yet been able to provide counseling service on it so that there is not any attempt to prevent and solve the problem. Apart from it, the inappropriate family background of the bullying-doers worsens interpersonal intelligence of the students.Â